2021
DOI: 10.1002/jobm.202100314
|View full text |Cite
|
Sign up to set email alerts
|

Effects of algal–bacterial ratio on the growth and cadmium accumulation of Chlorella salina–Bacillus subtilis consortia

Abstract: Algae-bacteria consortia have been proven effective in the removal of metal pollutants, but the effects of algal-bacterial ratio in the metal accumulation and resistance by this symbiotic system have not been systematically investigated. In this study, we set up consortia with various ratios of Chlorella salina-Bacillus subtilis, determined their growth, Cd accumulation, levels of intracellular glutathione (GSH), extracellular polysaccharide, phosphorus (P) in the culture medium, and functional groups of conso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Although the development of a proper model to exploit the full potential of microalgae-bacteria consortium is still far to be established [126], the use of Microalga Growth-Promoting Bacteria (MGPB), as defined in different publications, seems to be a promising strategy to increase algal biomass and reduce heavy metals, or other pollutants, concentration [127]. In support, Yu et al, reported a more efficient Cd accumulation when a higher bacteria concentration was added to the mixed system composed by Chlorella salina and Bacillus subtilis [128]. An efficient treatment of Cu mine wastewater was obtained using immobilized sulphate-reducing bacteria beads with microalgae biomass as the sole nutrient sources [129].…”
Section: Microalgal Potential For Hm Removal With a Special Focus On ...mentioning
confidence: 99%
“…Although the development of a proper model to exploit the full potential of microalgae-bacteria consortium is still far to be established [126], the use of Microalga Growth-Promoting Bacteria (MGPB), as defined in different publications, seems to be a promising strategy to increase algal biomass and reduce heavy metals, or other pollutants, concentration [127]. In support, Yu et al, reported a more efficient Cd accumulation when a higher bacteria concentration was added to the mixed system composed by Chlorella salina and Bacillus subtilis [128]. An efficient treatment of Cu mine wastewater was obtained using immobilized sulphate-reducing bacteria beads with microalgae biomass as the sole nutrient sources [129].…”
Section: Microalgal Potential For Hm Removal With a Special Focus On ...mentioning
confidence: 99%
“…Allam [40] carried out a comparative study on the bioremediation efficiency of HMs and dyes by individuals or consortia of bacteria (Bacillus subtilis, Rhizobium radiobacter and Sphingomonas paucimobilis) and found much higher removal efficiency results for Cd (96%). Yu et al [42] investigated the effects of algal-bacterial ratio on the Cd accumulation of Bacillus subtilis-Chlorella salina consortium and determined a lower value of Cd removal (51.66%) than the values in the present study.…”
Section: Cadmium (Cd)mentioning
confidence: 50%